Molecular epidemiology of chicken anemia virus in commercial farms in China - Jin Wenjie; Qian Kun; Eltahir Yassir M; Wang Pingping; Qin Aijian (Virology Journal, 2011)
Abstract Background Chicken anemia virus (CAV) is the causative agent of chicken infectious anemia (CIA). A high prevalence of CAV has been reported in China. However, VP1 sequences of Chinese isolates show no clear genotype clustering or correlation with geographic origin. Therefore, the present study aimed to detect and characterize CAV isolates from China based on sequence and phylogenetic analysis of the VP1, VP2 and VP3 genes. Results Of 460 spleen samples tested by PCR, 47 (10.22%) were found to be positive for CAV. A total of 25 CAV, approximately full genomes, from different commercial farms were characterized. Phylogenetic analysis of the Chinese CAV sequences together with strains from different countries resulted in four distinct groups (A-D) with significant high bootstrap values. The Chinese viral sequences were located as four different clusters within groups A and D. All the Chinese CAV genomes characterized in this study had glutamine (Q) at amino acid position 394, which indicated that all are highly pathogenic. Mutations associated with attenuation and weaker reactivity with monoclonal antibody 2A9 were absent in the Chinese sequences. Conclusions We revealed that CAV prevalence was lower than that reported previously in commercial farms in China. We also showed four distinct sequence groups (A-D), and genetic variability in local CAV sequences that could be divided into four groups based on phylogenetic analysis.